2022
DOI: 10.1186/s40364-022-00390-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multiomic approach for identification of novel immunotherapeutic targets in AML

Abstract: Background Immunotherapy of acute myeloid leukemia has experienced considerable advances, however novel target antigens continue to be sought after. To this end, unbiased approaches for surface protein detection are limited and integration with other data types, such as gene expression and somatic mutational burden, are poorly utilized. The Cell Surface Capture technology provides an unbiased, discovery-driven approach to map the surface proteins on cells of interest. Yet, direct utilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Overexpression of CD339/JAG1 in APL was the only consistent finding in the two datasets, in line with previous reports including both gene expression data from RNA-Seq and microarray analyses [ 27 ] or flow cytometry studies [ 28 ] Of note, differential expression in APL and other AML subtypes cannot be deduced from these earlier studies for all CD genes identified by our calculations, such as CD84 [ 29 ], CD88 [ 30 ], CD148 [ 23 , 31 ], CD210A/IL10RA, and CD227 [ 32 , 33 ]. However, all of these genes have been detected in cells from all hematopoietic lineages or AML blasts, and CD148 and CD210 have even been recently suggested as novel immunotherapeutic targets in AML [ 34 ], except forCD261/TNFRSF10A which we did not find in previous publications pointing to implications in AML or APL.…”
Section: Resultscontrasting
confidence: 54%
“…Overexpression of CD339/JAG1 in APL was the only consistent finding in the two datasets, in line with previous reports including both gene expression data from RNA-Seq and microarray analyses [ 27 ] or flow cytometry studies [ 28 ] Of note, differential expression in APL and other AML subtypes cannot be deduced from these earlier studies for all CD genes identified by our calculations, such as CD84 [ 29 ], CD88 [ 30 ], CD148 [ 23 , 31 ], CD210A/IL10RA, and CD227 [ 32 , 33 ]. However, all of these genes have been detected in cells from all hematopoietic lineages or AML blasts, and CD148 and CD210 have even been recently suggested as novel immunotherapeutic targets in AML [ 34 ], except forCD261/TNFRSF10A which we did not find in previous publications pointing to implications in AML or APL.…”
Section: Resultscontrasting
confidence: 54%
“…They identified three promising targets: CD148, ITGA4 and Integrin beta-7. Among these, Integrin beta-7 was the most favorable due to low or absent expression in healthy hematopoietic tissues [61]. In a recent scRNA-sec approach, two antigen targets-CSF1R and CD86 revealed potential targets for CAR T-cell therapy with broad expression on AML blasts accompanied by minimal toxicities toward relevant healthy cells and tissues [62].…”
Section: Safer Targets With Less 'On-target Off-tumor' Effectmentioning
confidence: 99%
“…42 Lin et al 138 confirmed that Glutamate-cysteine ligase catalytic (GCLC) is essential for cell growth, survival, clonogenicity, and leukemogenesis of AML cells but not for normal hematopoietic stem and progenitor cells (HSPCs), indicating that GCLC is a potential therapeutic target for AML. Köhnke et al 139 demonstrated a surfaceome detection method to investigate the whole AML surfaceome directly from raw patient samples and integrate these data with gene expression and mutational burden data, allowing for unbiased, genome-wide screening for target discovery in AML immunotherapy. Besides, the study of Ravasio et al 140 supported the use of LSD1i in combination therapy.…”
Section: Therapy Strategies In Amlmentioning
confidence: 99%
“…Besides, the integration of gene expression data and other relevant information can also yield valuable discoveries. 113,139,159,169 After integration, various analysis tools can be used to perform the analysis easier and more conveniently. Some AML studies utilized tools such as cBioPortal, Metascape, LinkedOmics, 150 and GEPIA, 11 while others require customized models and corresponding statistical or bioinformatics techniques to meet specific research needs.…”
Section: Public Resources For Aml Studiesmentioning
confidence: 99%
See 1 more Smart Citation